2012
DOI: 10.1111/j.1741-3737.2012.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations Among Intimate Partner Violence, Maternal Depressive Symptoms, and Maternal Parenting Behaviors

Abstract: The authors examined the relations among intimate partner violence (IPV), maternal depressive symptoms, and maternal harsh intrusive parenting. Using a cross-lagged, autoregressive path model, they sought to clarify the directionality of the relations among these 3 variables over the first 2 years of the child’s life. The results indicated that, in this diverse sample of families living in predominantly low-income rural communities (N = 705), higher levels of early IPV were associated with increases in materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 71 publications
3
60
1
Order By: Relevance
“…Caregivers may be preoccupied, may disengage from active caregiving, or may show intrusive or harsh parenting behavior (Gustafsson & Cox, 2012).…”
Section: Characteristics Of Ipvmentioning
confidence: 99%
“…Caregivers may be preoccupied, may disengage from active caregiving, or may show intrusive or harsh parenting behavior (Gustafsson & Cox, 2012).…”
Section: Characteristics Of Ipvmentioning
confidence: 99%
“…Whitaker, Haileyesus, Swahn, and Saltzman (2007) analyzing the Longitudinal Study of Adolescent Health (Add Health) found that women comprised 70% of perpetrators reporting nonreciprocal violence. Moreover, perpetration and victimization were correlated in many community studies (e.g., Caetano et al, 2008; Gustafsson and Cox, 2012; Jennings et al, 2012; Rhodes et al, 2009) demonstrating that much violence is bidirectional. Prior findings from the fourth interview of the TARS data (Alvira-Hammond et al, in press), for example, were consistent with those from other community studies (e.g., Jennings et al, 2012) in that nearly half (49%) of respondents who reported a physical altercation with a partner indicated that it was bidirectional, versus 19% who reported perpetration only and 32% who reported victimization only.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, IPV is associated with increases in maternal depressive symptoms (Gustafsson and Cox 2012) and often escalates around the time of pregnancy and birth (Campbell 2002). The FFCWS contains several measures of IPV; however, these measures tend to be worded in such a way that it is difficult to ascertain whether reports of IPV refer to past incidents or current, ongoing episodes of violence.…”
Section: Intimate Partner Violencementioning
confidence: 99%